Out to Lunch - Krulik, Nancy E.; John & Wendy (New York : Grosset & Dunlap, 2002)
Third-grader Katie Carew feels torn between her two best friends, but after wishing she were someone else, she morphs into Lucille, the lunchroom lady, and experiences life from the other side of the counter, with unexpected results
Keywords: Metamorphosis -- Juvenile fiction; Girls -- Juvenile fiction; Hamsters -- Juvenile fiction; School lunchrooms, cafeterias, etc -- Juvenile fiction; School lunchrooms, cafeterias, etc. -- Fiction; Food -- Fiction; Friendship -- Fiction; Magic -- Fiction